Case Report: Exceptional response to nivolumab plus cabozantinib in a patient with extrarenal clear cell renal cell carcinoma - Jansen, Caroline S.; Choi, Yujin; Evans, Sean T.; Greenwald, Rachel; Behnke, Joseph A.; Hartman, Caitlin; Kissick, Haydn; Harik, Lara R.; Bilen, Mehmet Asim (Frontiers in Oncology, 2023)
Extrarenal Clear Cell Renal Cell Carcinoma (eccRCC) is a rare type of RCC that arises in areas other than the kidney. Given its rarity, consensus guidelines for optimal treatment of eccRCC have not been established, and the literature is lacking any reports of patient response to systemic therapy and any reports of administration of immunotherapy to patients with eRCC. Here, we present the case of a patient in their 60s with eccRCC arising in the spleen. The patient underwent splenic resection, and due to disease recurrence, then received systemic therapy, with a combination of immunotherapy (IO) and tyrosine kinase inhibitor targeted therapy (VEGF-TKI).The patient had an excellent and durable response to this therapeutic regimen with minimal adverse effects, completing two years of therapy of nivolumab and cabozantinib. At the time of this report, the disease remains stable. This case demonstrates that combination therapy with IO+VEGF-TKI represents a reasonable and well-tolerated treatment option with activity in eccRCC and reveals interesting correlative data, including nests of stem-like CD8+T-cell infiltration in tumor tissue, which provide important biological context to this patient's exceptional therapeutic response.